2019
DOI: 10.1111/poms.12954
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Working Capital Financing Costs on the Efficiency of Trade Credit

Abstract: W e consider how trade credit can coordinate a two-echelon supply chain in the presence of supplier moral hazard and costly working capital financing. While trade credit resolves moral hazard problems in the absence of working capital financing costs, we show that this is not necessarily true when financial frictions make financing trade credit costly. We then show that trade credit along with an appropriately designed reverse factoring program can restore supply chain efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…Ebrahimi et al (2019) used the delay in payment contract as an incentive to coordinate a supply chain with stochastic, promotionaleffort-dependent demand. Devalkar and Krishnan (2019) examined the use of trade credit in decreasing moral hazard and adopting supply chain coordination in the presence of information asymmetry and financial friction. Ding and Wan (2020) studied supply chain coordination in the presence of capital constraints and production yield uncertainty.…”
Section: Combining Supply Chain Coordination and Operations-finance Imentioning
confidence: 99%
“…Ebrahimi et al (2019) used the delay in payment contract as an incentive to coordinate a supply chain with stochastic, promotionaleffort-dependent demand. Devalkar and Krishnan (2019) examined the use of trade credit in decreasing moral hazard and adopting supply chain coordination in the presence of information asymmetry and financial friction. Ding and Wan (2020) studied supply chain coordination in the presence of capital constraints and production yield uncertainty.…”
Section: Combining Supply Chain Coordination and Operations-finance Imentioning
confidence: 99%
“…The above literature has shown that the trade credit financing has a more important impact on the profit. Devalkar and Krishnan (2019) studied how trade credit coordinates the supply chain when considering the costly working capital financing of supplier. Gupta and Chutani (2019) studied the financing decision considering supply interruption, and found that the retailer can alleviate the impacts of supply disruption through advance sale financing.…”
Section: Literaturementioning
confidence: 99%
“…Trade credit is a risk-sharing and coordination mechanism that is widely offered by a dominant supplier to empower downstream wholesalers that commonly suffer from capital shortages ( Yang and Birge, 2018 , Devalkar and Krishnan, 2019 ). Lee and Rhee’s (2011) seminal study on SC coordination via trade credit examines channel coordination from a supplier’s perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Zhang et al (2014) examine how channel coordination is impacted by the simultaneous use of trade credit and a quantity discount contract. Focusing on moral hazards and working capital financing costs, Devalkar and Krishnan (2019) study a two-echelon SC and examine channel coordination. They find that reverse factoring programs combined with trade credit can improve SC efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation